War Cycle and Business Cycle Illustrated by the Period of 1962–2007 in the USA (Economic and Political Thought, 2014)
The article presents the research into interdependence of war and thephenomena of economic growth and a business cycle. The research is doneinto the period of 1962–2007 in the United States. It is empiric in characterand the main research tool is statistics.